Language diversity in a Mediterranean mediascape. (August 2018) - Pelillo-Hestermeyer, Giulia
Highlights: Linguistic diversity is examined in a Mediterranean transnational radio production. The performed diversity questions dominant representations of the Mediterranean. Localities at the periphery of mainstream mediascapes gain a new centrality. Language, discourse and journalistic practices display a specific transculturality. Media and linguistic analysis are applied to investigate a mediatized public sphere. Abstract: The article analyses a particular form of linguistic and cultural diversity performed in two radio magazines, Kantara and Mediterradio, produced as part of transnational media cooperation in the Mediterranean region. The analysis focuses on the interplay between language, discourse and journalistic practices, rooted in a specific journalistic and civic culture that aims at constructing a shared public sphere in opposition to mainstream media reports about the Mediterranean. The results demonstrate a particular polycentrism and mobility of media production, observable in language, discourse and journalistic features, in which localities traditionally considered "at the periphery" of global media flows, such as the Western Mediterranean islands Sicily, Sardinia and Corsica, constitute crucial points. The article approaches the resulting multilayered transculturality by grasping the specific culture inspiring the work of the network, and the multiple identities related to it. To this aim, a transdisciplinary approach integrating sociolinguistics, discourse, media and cultural studies with a specific focus on mediatized transcultural communication is developed.